(untitled) (Journal of the College of Basic Education, 2022)
Education in our time is considered one of the most important areas of life, as education has never, throughout its long history, demonstrated its social function in its dimensions and its role in bringing about comprehensive changes in our society, as it happened to it in the current century, especially at its end.